2020
DOI: 10.3389/fneur.2020.588377
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss and Irritability Reporting Without Vestibular Differences in Explosive Breaching Professionals

Abstract: Background: Blast exposure is a potential hazard in modern military operations and training, especially for some military occupations. Helmets, peripheral armor, hearing protection, and eye protection worn by military personnel provide some acute protection from blast effects but may not fully protect personnel against cumulative effects of repeated blast overpressure waves experienced over a career. The current study aimed to characterize the long-term outcomes of repeated exposure to primary blast overpressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…As with previous research, the most consistent findings emerged primarily for conditions that were neurological, hearing-related, or mental health-related. Specifically, these findings provide yet more evidence of the association between overpressure exposure (including single HLB, repeated HLB, and occupational LLB exposure) and hearing loss and tinnitus diagnosis ( 1 , 11 13 , 17 , 33 – 35 ). Additionally, this research builds on previous research reporting on the adverse reproductive health consequences of HLB in that it reports that such effects occur for those who work occupations at high (but not low) risk for occupational exposure to LLB ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 75%
“…As with previous research, the most consistent findings emerged primarily for conditions that were neurological, hearing-related, or mental health-related. Specifically, these findings provide yet more evidence of the association between overpressure exposure (including single HLB, repeated HLB, and occupational LLB exposure) and hearing loss and tinnitus diagnosis ( 1 , 11 13 , 17 , 33 – 35 ). Additionally, this research builds on previous research reporting on the adverse reproductive health consequences of HLB in that it reports that such effects occur for those who work occupations at high (but not low) risk for occupational exposure to LLB ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 75%
“…It is important to remember that SOT VES scores are not diagnostic and do not reveal potential damage to the vestibular system but rather they reveal balance problems when using vestibular information for postural control 34 . Breachers were thoroughly examined in a separate clinic in this outpatient study with specific vestibular testing and found to have no vestibular abnormalities as a group 29 . A closer examination of the two individuals (10%) with clinically abnormal SOT VES scores showed one individual also scored abnormally for SOT VIS and the other had a history of prior head trauma symptomology (e.g., memory problems, ringing in ears, etc).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of neurophysiological and behavioral measurements were collected in this study and specific findings related to those measures have been reported elsewhere. 28,29 The focus of the current report is objective assessments of balance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations